2011
DOI: 10.1093/humrep/der246
|View full text |Cite
|
Sign up to set email alerts
|

Stress, distress and outcome of assisted reproductive technology (ART): a meta-analysis

Abstract: Small but significant associations were found between stress and distress and reduced pregnancy chances with ART. However, there were a limited number of studies and considerable between-study heterogeneity. Taken together, the influence of stress and distress on ART outcome may appear somewhat limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
147
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(163 citation statements)
references
References 62 publications
8
147
1
7
Order By: Relevance
“…In the study, researchers from Denmark found no association between anxiety disorders and the effects of ART treatment [20]. However, the authors underline a large heterogeneity of the study groups and a fairly low number of studies included in the meta-analysis.…”
Section: The Influence Of Anxiety On the Effects Of Infertility Treatmentioning
confidence: 87%
See 1 more Smart Citation
“…In the study, researchers from Denmark found no association between anxiety disorders and the effects of ART treatment [20]. However, the authors underline a large heterogeneity of the study groups and a fairly low number of studies included in the meta-analysis.…”
Section: The Influence Of Anxiety On the Effects Of Infertility Treatmentioning
confidence: 87%
“…In a study conducted in the USA on a group of 202 women undergoing an IVF procedure for the first time, a diagnosis of depression had no effect on the efficacy of IVF [19]. Also a meta-analysis by Mathiessen et al did not reveal a significant influence of depression diagnosed before ART therapy on the number on achieved pregnancies [20].…”
Section: The Influence Of Depression On the Effects Of Infertility Trmentioning
confidence: 95%
“…Female factor infertility can be divided into several categories: cervical or uterine, ovarian, tubal, and other. 6 The diagnosis and treatment of this disorder stands out as one of the most rapidly evolving area in medicine. Experience has shown that majority of pelvic pathology in infertile women is frequently not well appreciated by routine pelvic examinations and the usual diagnostic procedures.…”
mentioning
confidence: 99%
“…During the various stages of infertility treatment ranging from ovulation induction, artificial insemination and in vitro fertilization, women experience various psychological stresses including physical stress, anxiety, depression, and exposure of sex life [3]. Also, in Korea's Confucian culture, infertility is recognized as a problem that is not easy to reveal in society [4], and the stigma characteristic of the problem is serious, for example, it makes the subject reluctant to talk about their problems and causes a lack of social support [5].…”
Section: The Need For Researchmentioning
confidence: 99%